Landsmøtet 1917 og samebevegelsen i nord - Bjørklund, Ivar (Heimen, 2017)
Source at http://doi.org/10.18261/ISSN.1894-3195-2017-02-02 THE SÁMI NATIONAL ASSEMBLY IN 1917 AND THE SÁMI MOVEMENT IN THE NORTH The Sámi national assembly held in Trondhjem in 1917 is considered to be the very first organized political opposition from the Norwegian Sámi. However, among the 150 persons attending, only three Sámi were from Northern Norway – an area where 90% of the Sámi population lived. The participants were Sámi from the southern parts of Norway, all involved in reindeer herding, which was the main topic to be discussed at the meeting. The Norwegian authorities were about to make a new law on reindeer herding, and the southern Sámi organized the meeting to voice their interests – a meeting which was supported and partly financed by the government. At the same time, a strong Sámi political movement had been established in the north. Two large meetings were held in 1919 and 1920, but without any official attendance or financial support. They presented themselves as indigenous and stressed their «fight for survival». They insisted that the ongoing Norwegian assimilation policy had to end and the Sámi language should be accepted and taught in school. Thus, the northern Sámi saw fewer interests in the political agenda of their southern brethren, which were centred around reindeer herding legalities. The authorities, on their side, saw no interest at all in supporting the ethnopolitical claims from the north